KETIMPANGAN KETIMPANGAN AKSES TERHADAP TEKNOLOGI INFORMASI DENGAN PENDEKATAN HUMAN OPPORTUNITY INDEX (HOI) - Riyadi Riyadi; Putri Larasaty (Seminar Nasional Official Statistics, 2020)
Inequality is one of the crucial problems in society that may not be fully resolved. This paper analyzes the inequality of opportunity in accessing to technology and information in Indonesia. This study uses data from SUSENAS Kor 2019 form Statistics Indonesia-BPS. The analysis uses a method the Human Opportunity Index (HOI) by the World Bank. The HOI measures the contribution of individuals’ socio-economic and demographic circumstances to inequality of opportunity in accessing to technology and information services. The logit model is also used to determine the socio-economic and demographic factors of accessing to technology and information. The results of empirical analysis show that there are still wide opportunities for access to technology and information services in Eastern Indonesia and Western Indonesia. In addition, the conditions of expenditure per capita and residential areas are the most dominant factors towards the inequality of opportunity in accessing to technology and information. This suggests that household poverty dan residential areas have a crucial role in determining equitable access to technology and information.